The Effect of Competence and Job Placement on Employee Performance at the Regional Revenue and Asset Management Agency of Sibolga City - Widya Putri Hasanah Hutagalung; Kaharuddin Kaharuddin; Khairil Safli Pohan (Devitara Innovations, 2026)
This study aims to analyze the influence of competence and job placement on employee performance at the Regional Revenue, Finance, and Asset Management Agency (BPKAD) of Sibolga City. The research sample consisted of 60 employees selected through purposive sampling. Data were collected using a questionnaire that had been tested for validity and reliability and were analyzed using multiple linear regression. The results indicate that competence has a strong correlation with performance (r = 0.740), while job placement has a correlation of 0.667. Simultaneously, competence and job placement contribute 63.9% to employee performance. The t-test and F-test results show that both variables significantly influence performance, either partially or simultaneously. These findings highlight the importance of employee competence development and appropriate job placement according to skills and job characteristics to enhance organizational performance.